Evaluation of H2O2 electrogeneration and decolorization of Orange II azo dye using tungsten oxide nanoparticle-modified carbon - Paz, Edson C. (2018)
In this paper, we report on the development of a new catalyst for H2O2 electrogeneration for the preparation of a gas diffusion electrode (GDE) for water treatment by electrochemical advanced oxidation processes (EAOPs). Catalysts based on tungsten oxide nanoparticles on Vulcan XC72 and Printex 6L carbons were studied by X-ray diffraction (XRD), transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), contact angle measurements and oxygen reduction reaction (ORR) assays using a rotating ring-disk electrode (RRDE) system. The WO2.72/Vulcan XC72 (1% w/w of W) catalyst was used for the construction of a GDE due to its notable performance in H2O2 electrogeneration, its good current efficiency for H2O2 electrogeneration and its lower energy consumption. Thus, the WO2.72/Vulcan XC72 GDE cathode was combined with a Pt or boron-doped diamond (BDD) anode for the decolorization of 0.260 mM Orange II azo dye solutions by EAOPs. The decolorization efficiency was in the following sequence: photodegradation (PD) < Pt/anodic oxidation (AO) ≈ BDD/AO < BDD/electro-Fenton (EF) ≈ BDD/photoelectro-Fenton (PEF) < Pt/EF < Pt/PEF. The Orange II decolorization efficiency by Pt/PEF was equal to or higher than that reported in similar studies. Moreover, the results showed that an Orange II decolorization percentage of 77% in the PEF and EF processes with a Pt anode was due to the WO2.72/Vulcan XC72 cathode, showing that this catalyst is a promising candidate for application in EAOPs.